Self-monitoring or reliance on newswire services: How do financial market participants process central bank news? - Bernd Hayo; Matthias Neuenkirch (Universität Trier, Fachbereich IV – Volkswirtschaftslehre, 2014)
We study how financial market participants process news from four major central banks - the Bank of England (BoE), the Bank of Japan (BoJ), the European Central Bank (ECB), and the Federal Reserve (Fed), using a novel survey of 450 financial market participants from around the world. Our results indicate that, first, respondents rely more on newswire services to learn about central bank events than on self-monitoring. In general, the Fed is watched most closely, followed by the ECB, the BoE, and the BoJ. Second, we estimate ordered probit models to relate the two different types of central bank watching to the perceived importance of central bank events and the reliability of media coverage. Our results indicate that financial agents have to rely on newswire services to appropriately cope with a globalised market environment and digest news. However, when respondents consider an event particularly important, they tend to selfmonitor it, especially when the event is taking place in their home region.
Keywords: D83; E52; E58; 330; Central Bank Communication; Financial Market Participants; Information Processing; Interest Rate Decisions; Newswire Services; Reliability; Survey